2016
DOI: 10.1016/j.physbeh.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Fuel not fun: Reinterpreting attenuated brain responses to reward in obesity

Abstract: There is a well-established literature linking obesity to altered dopamine signaling and brain response to food-related stimuli. Neuroimaging studies frequently report enhanced response in dopaminergic regions during food anticipation and decreased responses during reward receipt. This has been interpreted as reflecting anticipatory “reward surfeit”, and consummatory “reward deficiency”. In particular, attenuated response in the dorsal striatum to primary food rewards is proposed to reflect anhedonia, which le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 111 publications
(135 reference statements)
8
48
0
Order By: Relevance
“…Collectively, these findings suggest that the A1 allele is associated with enhanced error, but weaker reward outcome signal generation in the context of overall heightened reward sensitivity [99]. Supporting this interpretation, another study recently reported enhanced midbrain response in A1carriers vs. non-carriers upon the generation of positive error signals during a probabilistic learning task [34].…”
Section: Taqia Polymorphism (Rs1800497)mentioning
confidence: 88%
See 1 more Smart Citation
“…Collectively, these findings suggest that the A1 allele is associated with enhanced error, but weaker reward outcome signal generation in the context of overall heightened reward sensitivity [99]. Supporting this interpretation, another study recently reported enhanced midbrain response in A1carriers vs. non-carriers upon the generation of positive error signals during a probabilistic learning task [34].…”
Section: Taqia Polymorphism (Rs1800497)mentioning
confidence: 88%
“…As such, it has been suggested that the decreased response to predicted milkshake corresponds to a weaker outcome signal while the increased response to unpredicted milkshake reflects an enhanced error signal. At the same time it is proposed that the enhanced responses to food cues reflect an overall heightened reward sensitivity in obesity [99]. …”
Section: Taqia Polymorphism (Rs1800497)mentioning
confidence: 99%
“…Individuals carrying risk alleles are at risk of weight gain related to hypo-responsivity to food cues or taste receipt within dorsal striatal regions (caudate) [85, 86], whereas in non-carriers, hyper-responsivity promotes obesity risk. While the interpretation of such findings as a deficit in experienced reward has been debated [87, 88], inherited variability in dopamine-dependent neural signaling clearly influences components of CNS appetite regulation and obesity risk directly [89, 8, 90] and via interactions with other risk genes [84, 91]. …”
Section: Evidence That Response To Visual Food Cues Is An Inherited Tmentioning
confidence: 99%
“…Although occasional overeating is a common phenomenon in our obesogenic environment, chronic overeating often results in obesity. Recent theory suggests that, rather than hyper-or hyposensitivity to food rewards, obesity may be related to impaired outcome-based learning [12][13][14] . Impaired reward and punishment learning may maintain overeating in obesity by leading to compulsive over-selection of actions directed at food rewards and/or decreased sensitivity to negative consequences associated with overeating, such as an uncomfortably full feeling or long-term health risks.…”
mentioning
confidence: 99%
“…Studies investigating cue-reward learning in relation to obesity have provided some evidence for impaired learning from positive 15,16 as well as from negative outcomes 13,14 . Others have hypothesized that obesity is accompanied by learning impairments that generalize across outcomes 12 . Here, we hypothesize that a mindfulness-based intervention targeting undesired eating behavior would improve outcome-based reversal learning, which could be in a manner that depends on the valence of the outcome or independent of valence.…”
mentioning
confidence: 99%